The Antislavery debate : capitalism and abolitionism as a problem in historical interpretation - Haskell, Thomas L., 1939-; Davis, David Brion; Ashworth, John, 1950-; Bender, Thomas (Berkeley : University of California Press, 1992)
Publisher description: This volume brings together one of the most provocative debates among historians in recent years. The center of controversy is the emergence of the antislavery movement in the United States and Britain and the relation of capitalism to this development. The essays delve beyond these issues, however, to raise a deeper question of historical interpretation: What are the relations between consciousness, moral action, and social change? The debate illustrates that concepts common in historical practice are not so stable as we have thought them to be. It is about concepts as much as evidence, about the need for clarity in using the tools of contemporary historical practice.
Introduction / Thomas Bender -- Part 1. The problem of slavery in the age of revolution, 1770-1823 / David Brion Davis. 1. What the abolitionists were up against -- 2. The Quaker ethic and the antislavery international -- 3. The preservation of English liberty, I -- Part 2. The AHR debate. 4. Capitalism and the origins of the humanitarian sensibility, part 1 / Thomas L. Haskell -- 5 Capitalism and the origins of the humanitarian sensibility, part 2 / Thomas L. Haskell -- 6. Reflections on abolitionism and ideological hegemony / David Brion Davis -- 7. The relationship between capitalism and humanitarianism / John Ashworth -- 8. Contention and hegemonic interest in the debate over antislavery : a reply to Davis and Ashworth / Thomas L. Haskell -- Part 3. The debate continued. 9. Capitalism, class, and antislavery / John Ashworth -- 10. The perils of doing history by ahistorical abstraction : a reply to Thomas L. Haskell's AHR forum reply / David Brion Davis.
Includes bibliographical references and index.
Mode of access: Internet.
Keywords: Capitalism -- United States; Capitalism; Antislavery movements -- United States; Antislavery movements